2017
DOI: 10.3389/fmicb.2017.01634
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Phenanthrene Degrading Bacteria from Diesel Fuel-Contaminated Antarctic Soils

Abstract: Antarctica is an attractive target for human exploration and scientific investigation, however the negative effects of human activity on this continent are long lasting and can have serious consequences on the native ecosystem. Various areas of Antarctica have been contaminated with diesel fuel, which contains harmful compounds such as heavy metals and polycyclic aromatic hydrocarbons (PAH). Bioremediation of PAHs by the activity of microorganisms is an ecological, economical, and safe decontamination approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“…strain Vi 1, respectively. The results of this study is also in agreement with Gran-Scheuch et al (2017) who, reported that isolated bacterial strain Sphingobium xenophagum D43FB was capable of degrading phenanthrene in the presence of heavy metals present in diesel.…”
Section: Resultssupporting
confidence: 92%
“…strain Vi 1, respectively. The results of this study is also in agreement with Gran-Scheuch et al (2017) who, reported that isolated bacterial strain Sphingobium xenophagum D43FB was capable of degrading phenanthrene in the presence of heavy metals present in diesel.…”
Section: Resultssupporting
confidence: 92%
“…As one of the most common structural units of organic compounds in nature, the benzene ring and its derivatives are extensively used in industrial production, including daily supplies, agro-products, energy products, etc. Although some structural properties of these compounds make them recalcitrant to degradation, many aromatic-degrading microbes have been isolated ( Fuchs et al, 2011 ; Xu et al, 2015 ), with metabolic pathways and mechanisms reported for some ( Chauhan et al, 2000 ; Zhang et al, 2012 ; Shah et al, 2014 ; Gran-Scheuch et al, 2017 ), but not all ( Goncalves et al, 2006 ; Zhou et al, 2015 ). These works and hundreds of others have advanced our knowledge of aromatic compounds degradation.…”
Section: Introductionmentioning
confidence: 99%
“…However, biodegradation of PAHs is gaining much attention due to the extravagant cost of the aforementioned conventional methods and environmental concerns. Therefore, literature also furnishes much information from original research articles [132,133] to review articles [10,134] on PAHs biodegradation. Scopus, a well-recognized database for scientific literature search, generated 406 entries for keywords "naphthalene and biodegradation", accessed on 15/11/2019.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%